2021
DOI: 10.3389/fmicb.2021.604662
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth and Drought Tolerance-Promoting Bacterium for Bioremediation of Paraquat Pesticide Residues in Agriculture Soils

Abstract: Thailand is an agricultural country. However, agricultural productivity relies on the heavy use of herbicides, especially paraquat. Paraquat accumulation is emerging as a problem in an ever-growing portion of agricultural land. Paraquat residues are toxic to plants, animals, and aquatic organisms in the environment. Biological remediation is a process that can mitigate agricultural chemical contaminants. One of the interesting bioremediators is bacteria. Not only do certain soil bacteria remediate paraquat, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 59 publications
1
17
0
1
Order By: Relevance
“…showed that the bacteria can grow best at pH of 6.5 with an optimum temperature of 30 ºC. Similar optimum temperatures and slightly higher pH of 7.0 have been reported on paraquat degradation by Bacillus aryabhattai [27].…”
Section: Discussionsupporting
confidence: 79%
“…showed that the bacteria can grow best at pH of 6.5 with an optimum temperature of 30 ºC. Similar optimum temperatures and slightly higher pH of 7.0 have been reported on paraquat degradation by Bacillus aryabhattai [27].…”
Section: Discussionsupporting
confidence: 79%
“…Contrarily, some chemicals pesticides may induce toxicity to beneficial rhizospheric microorganisms even at extremely low doses ( Shahid et al., 2021d ). Likewise our study, Bacillus aryabhattai strain MoB09, recovered from agricultural soils contaminated with paraquat herbicide, utilized herbicide as carbon source under controlled condition and grew well ( Inthama et al., 2021 ). In addition, a similar study conducted by Aroua et al.…”
Section: Resultsmentioning
confidence: 82%
“…Las bacterias y los hongos son los principales degradadores. Entre los aislados bacterianos destacan Bacillus, Pseudomonas, Flavobacterium, Arthrobacter, Diaphorobacter, Klebsiella, Ochrobactrum, Agrobacterium, Burkholderia, Kocuria, Archromobacter, Sphingomonas, Chromohalobacter, entre otros que han sido reportados como degradadores de plaguicidas (Ataikiru et al, 2020;Inthama et al, 2021). Las condiciones ambientales, en particular la presencia o ausencia de oxígeno tiene una influencia notable en la degradación de plaguicidas (Reineke, 2001).…”
Section: Plaguicidasunclassified